2019
DOI: 10.3389/fcimb.2019.00191
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Bloodstream Infections in Patients at a University Hospital: Virulence Factors and Clinical Characteristics

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) isolates are responsible for many bloodstream infections. The aim of this study was to characterize E. coli isolated from the bloodstreams of patients ( n = 48) at the University Hospital in Brazil. Epidemiological data were obtained through the analysis of medical records and laboratory tests. By PCR analysis, we investigated the presence of virulence factors (VFs), pathogenicity islands (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 54 publications
9
69
0
5
Order By: Relevance
“…Also, it was found associated with isolates of urinary tract infections that may give rise to bacteremia. 65,66 This study showed that traT was more common among E. coli isolated from urine and blood samples (59.1% and 55.5%, respectively). E. coli with serum resistance were highly virulent, as they can escape the complement system and promote serum survival and increase the risk of developing septic shock and the increase in mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Also, it was found associated with isolates of urinary tract infections that may give rise to bacteremia. 65,66 This study showed that traT was more common among E. coli isolated from urine and blood samples (59.1% and 55.5%, respectively). E. coli with serum resistance were highly virulent, as they can escape the complement system and promote serum survival and increase the risk of developing septic shock and the increase in mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Their adhesin FimH binds to glycosylated uroplakin and α1β3 (Korhonen et al, 1985;Guyer et al, 2000,? ;Russo et al, 2001;Bingen-Bidois et al, 2002;Johnson et al, 2002Johnson et al, , 2004Johnson et al, , 2008Marrs et al, 2002;Bonacorsi et al, 2003;Russo, 2003;Srinivasan et al, 2003;Buckles et al, 2004;Bonacorsi and Bingen, 2005;Parham et al, 2005a;Rendón et al, 2007;Restieri et al, 2007;Ananias and Yano, 2008;Henderson et al, 2009;Schubert et al, 2010;Ejrnaes et al, 2011;Mahjoub-Messai et al, 2011;Vejborg et al, 2011;Lehti et al, 2012;Qin et al, 2013;Tarchouna et al, 2013;Firoozeh et al, 2014;Basmaci et al, 2015;Nagarjuna et al, 2015;Wijetunge et al, 2015;Beck et al, 2016;Cordeiro et al, 2016;Lee and Lee, 2018;Daga et al, 2019;Nojoomi and Ghasemian, 2019;Raimondi et al, 2019;Sarowska et al, 2019 integrins covering the apical surface of uroepithelium cells, thereby promoting the invasion of host cells and the development of IBCs (Connell et al, 1996;Martinez et al, 2000;Gunther et al, 2002;Mysorekar and Hultgren, 2006;…”
Section: Adhesins Encoded or Regulated By Paismentioning
confidence: 99%
“…In addition to the above-mentioned properties, IncF plasmids also possessed virulence genes which can contribute to the fitness of bacterial clones inside mammalian hosts. For example, the traT gene related to serum resistance was found on every bla CTX-M -harboring IncF plasmid, except for IncF (F24:A-:B1), and this gene has been consistently associated with urinary tract infections and sepsis in humans (71)(72)(73)(74). Similarly, hlyF (hemolysin), iutA (iron uptake), and ompT (outer membrane protease) genes present on some of the bla CTX-M -IncF plasmids are very commonly found in avian pathogenic E. coli (75).…”
Section: Fig 7 Legend (Continued)mentioning
confidence: 99%